The Difference Effect Of Explosion Power Of Arm Muscle Exercise And Flexibleness Exercise Observed From Intensity Of Exercise Toward Ability In Front Handspring Gymnastics Athlete In Gymnastics Club Of Semen Padang - Deffri Anggara; Feby Elra Perdima (Hanoman Journal: Physical Education and Sport, 2021)
This research aims to explain the differences effect of explosion power of arm muscle exercise and flexibleness exercise with 50:50%  intensity by explotion power of arm muscle and flexibleness exercising with intensity 70:30% toward front handspring ability of gymnastics athlete in PT Semen Padang Club. The method of this research is quasi experimental method. The population of this research is 31 athletes, but the sample was obtained through purposive random sampling, so it was got 20 female athletes. The data of ability test front handspring aims to get information about ability of front handspring artistics gymnastics athletes of PT Semen Padang Club.Analysis data result shows that: (1) explosion power of arm muscle and flexibleness exercises with 50:50% intensity give significant influence toward ability of front handspring gymnastics athlete in PT Semen Padang Gymnastics Club. The increasing ability of front handspring is 4,1, (2) explosion power of arm muscle exercise and flexibleness exercise with 70:30 % give significant influence toward ability of front handspring gymnastics athlete in PT Semen Padang Gymnastics Club. The increasing ability of front handspring is 7,8, (3) There is difference between explosion power of arm muscle exercise and flexibleness exercise with 50:50% intensity and 70:30% intensity toward ability of front handspring gymnastics athlete in gymnastics club of PT Semen Padang, and explosion power of arm muscle exercise method and flexibleness exercise with 70:30% intensity is better than 50:50% intensity.